Isolation of Flaccidine, 3-Sitostenone and β-Sitosterol-3-O-β-D-glucopyranoside from Polygonum hydropiper and Evaluation of their Antimicrobial Activities - Sultana, Rajia; Nath, Ranjit K.; Hossain, Rashadul (Asian Journal of Chemistry, 2019)
Flaccidine, 3-sitostenone and β-sitosterol-3-O-β-D-glucopyranoside were isolated from aerial part of medicinal plant Polygonum hydropiper. These compounds were isolated upon repeat column chromatography, HPTLC, RP-18 reverse phase column of dichloromethane and ethyl acetate fractions of the crude methnolic extract. The structures of the isolated compounds were identified by spectroscopic technique. Antimicrobial activities of these compounds against some of bacteria and phyto-pathogenic fungus have been investigated in this study.